Immersive virtual reality game for cognitive-empathy education: Implementation and formative evaluation - Jeon, Hayoung; Jun, Yumi; Laine, Teemu H.; Kim, Eunha (Education and Information Technologies, 2024)
Empathy is an essential human skill that can be divided into two types: (i) cognitive empathy, which is the capacity of understanding others’ thoughts and emotions; and (ii) affective empathy, which is the capacity to feel others’ emotional states. Many educational contents exist for both types, and immersive virtual reality (VR) has been shown to be effective for empathy education. However, there is a lack of educational content on recognizing and accepting that people can have different perspectives and feelings in the same situation, which is a prerequisite for cognitive empathy. To this end, we developed an immersive VR game “Mysterious Museum” where the player solves various puzzles based on ambiguous images and three-dimensional models. Moreover, we implemented six versions of a level in the game based on design concepts for camera perspective (combinations of first-person and third-person with camera techniques) and content exhibition (gallery, conveyor belt). We then conducted a mixed-method formative evaluation with 19 participants (11 females, eight males, average age 25.4 years) measuring usability of the game, as well as cybersickness and preferences for the design concepts. The game’s usability was satisfactory except for the quality of instructions. Moreover, the conveyor belt, where the player does not need to move, was preferred over the gallery, while the fixed first-person perspective was the most preferred camera perspective. The latter along with the conveyor belt exhibition method caused the least cybersickness. These results can be useful to designers, developers, researchers, and psychologists interested in VR-based empathy education.
Keywords: Cognitive empathy; Cybersickness; Empathy education; Game; User experience; Virtual reality